Daratumumab monotherapy in patients with heavily pretreated relapsed or refractory multiple myeloma: final results from the phase 2 GEN501 and SIRIUS trials. Issue 6 (June 2020) - Usmani, Saad Z; Nahi, Hareth; Plesner, Torben; Weiss, Brendan M; Bahlis, Nizar J; Belch, Andrew; Voorhees, Peter M; Laubach, Jacob P; van de Donk, Niels W C J; Ahmadi, Tahamtan; Uhlar, Clarissa M; Wang, Jianping; et al.
Summary: Background: Daratumumab showed encouraging efficacy as monotherapy in patients with heavily pretreated multiple myeloma in the GEN501 and SIRIUS studies. Here we report a pooled, post-hoc final analysis of these two studies. Methods: GEN501 was an open-label, multicentre, phase 1–2, dose escalation and expansion study done in the Netherlands, the USA, Sweden, and Denmark. Eligible patients had multiple myeloma and had relapsed or were refractory to 2 or more previous lines of treatment that included a proteasome inhibitor or an immunomodulatory drug. SIRIUS was an open-label, multicentre, phase 2 study done in Canada, Spain, and the USA, in which eligible patients with multiple myeloma had received 3 or more previous lines of therapy, including a proteasome inhibitor or an immunomodulatory drug, or were double refractory. In both studies, eligible patients were aged 18 years or older and had an Eastern Cooperative Oncology Group performance status of 2 or less. In part 2 of GEN501, patients were given intravenous daratumumab 16 mg/kg once per week for 8 weeks, twice per month for 8 doses, and then once per month until disease progression. In part 2 of SIRIUS, patients received intravenous daratumumab 16 mg/kg once per week for 8 weeks, twice per month for 16 weeks, and once per month until disease progression. The primary endpoints (safety in GEN501 and overall response rate in SIRIUS) have previously been reported. These trials are registered on ClinicalTrials.gov, NCT00574288 (GEN501) and NCT01985126 (SIRIUS). Findings: Patients were enrolled in GEN501 from March 27, 2008, until May 30, 2014, and in SIRIUS from Sept 30, 2013, until May 5, 2014. The combined analysis included 148 patients who received daratumumab 16 mg/kg (42 patients in GEN501 part 2; 106 patients in SIRIUS), with a median follow-up of 36·6 months (IQR 34·5–38·2). Patients had received a median of 5 previous lines of therapy (IQR 4–7), and 128 (87%) of 148 patients were double refractory. The overall response rate was 30·4% (95% CI 23·1–38·5), including 20 (14%) of 148 patients with very good partial response or better (8·5–20·1) and seven (5%) patients reporting complete response or better (1·9–9·5). Among 45 responders, the median duration of response was 8·0 months (95% CI 6·5–14·7). Median overall survival was 20·5 months (95% CI 16·6–28·1), with a 3-year overall survival rate of 36·5% (28·4–44·6). The most common grade 3–4 treatment-emergent adverse events (TEAEs) were anaemia (grade 3, 26 [18%] of 148 patients; no grade 4 events) and thrombocytopenia (grade 3, 13 [9%] of 148 patients; grade 4, 8 [5%] of 148 patients). Serious drug-related TEAEs occurred in 13 (9%) of 148 patients. There were no treatment-related deaths. Interpretation: In this analysis, daratumumab 16 mg/kg monotherapy showed durable responses and there were no new safety concerns with longer follow-up. Funding: Janssen Research & Development.